2010
DOI: 10.1007/s11123-010-0189-8
|View full text |Cite
|
Sign up to set email alerts
|

A note on testing for complementarity and substitutability in the case of multiple practices

Abstract: Recent empirical studies of firm-level performance have tested complementarity in the case of multiple practices. These papers have drawn conclusions using potentially biased estimates of pair-wise interaction effects. We develop a consistent and simple testing framework and test it against alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 28 publications
2
80
0
Order By: Relevance
“…Therefore, we place a caveat on these results. Finally, as an additional check, we checked and found that the outcomes of the test according to Carree, Lokshin, and Belderbos (2011) testing procedure (not tabulated) are consistent with our reported results.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Therefore, we place a caveat on these results. Finally, as an additional check, we checked and found that the outcomes of the test according to Carree, Lokshin, and Belderbos (2011) testing procedure (not tabulated) are consistent with our reported results.…”
Section: Resultssupporting
confidence: 59%
“…Carree, Lokshin, and Belderbos (2011) show equivalence between the exclusive binary variable approach and non-exclusive binary variable approach (see Equation (9), 265.We use exclusive dummy variable approach in our tests.…”
Section: Discussionmentioning
confidence: 95%
“…Since we have multiple components of intangible assets which are quantitative in nature, we follow a recent methodology by Carree et al (2011) for all values (x 1 , x 2 , x 3 , x 4 , x 5 , x 6 , x 7 ) with the inequality being strictly positive for at least one value. The denition for substitutability applies accordingly; the cross derivatives have to be non-positive with at least one strictly negative.…”
Section: Complementarity Between Intangible Assetsmentioning
confidence: 99%
“…In order to detect complementary or substitutive relationships we follow a recent test approach proposed by Carree et al (2011). The empirical analysis is based on the Mannheim Innovation Panel (MIP), the German contribution to the European-wide Community Innovation Surveys (CIS).…”
Section: Introduction Introductionmentioning
confidence: 99%
“…Several studies have examined possible complementarity between technologies using the sign and significance of the effect of technology interactions on productivity (Dorfman, 1996;Stoneman, 2002;Caswell and Zilberman, 1985;Ichniowski, Shaw and Prennushi, 1997;Poppo and Zenger, 2002;and Carree,Lokshin and Belderbos, 2011). All past empirical strategies have suffered the curse of dimensionality which forces the consideration of only a small number of possible technologies.…”
Section: Introductionmentioning
confidence: 99%